Scaffold Biomaterials and Nano-Based Therapeutic Strategies for Skeletal Muscle Regeneration - Vilos-Ortiz, C; Cabello-Verrugio, C; Tacchi, F; Orozco-Aguilar, J (Future Medicine Ltd., 2021)
Skeletal muscle is integral to the functioning of the human body. Several pathological conditions, such as trauma (primary lesion) or genetic diseases such as Duchenne muscular dystrophy (DMD), can affect and impair its functions or exceed its regeneration capacity. Tissue engineering (TE) based on natural, synthetic and hybrid biomaterials provides a robust platform for developing scaffolds that promote skeletal muscle regeneration, strength recovery, vascularization and innervation. Recent 3D-cell printing technology and the use of nanocarriers for the release of drugs, peptides and antisense oligonucleotides support unique therapeutic alternatives. Here, the authors present recent advances in scaffold biomaterials and nano-based therapeutic strategies for skeletal muscle regeneration and perspectives for future endeavors. © 2021 Future Medicine Ltd.